Analisis Kualitatif Persepsi Visuospasial Muslim Milenial Urban Indonesia Terhadap Manasik Haji/Umrah Virtual - Nugroho, Adi; Moeksin, Ahmad Gamaludin; Maula, Akbar Ibrahim; Widyasari, Siti Mahrimah (Kartala, 2022)
The article presents the findings from a phenomenological, qualitative research study that explored the personal constructs of urban millennials Muslim in Indonesia in virtual Hajj/Umrah training (manasik). The focus of the study was to dig and assess the informer’s perception about doing the pilgrimage in the midst of pandemic as well as their responses to the spatial concept of a virtual manasik. In-depth interview accompanied with visual stimulus of a website showcasing a virtual 3D 360º of Kaaba was done to Muslim informers in order to collect data. The sample consisted of five Muslim informers, within the range age of 30 to 40 years old, male and female of which have had an experience of conducting umrah. Literature study and content analysis were also undertaken to provide a defensible conclusion. In general, informers who gave their insights about the training being carried out in Indonesia did not provide a comprehensive picture about the real condition and live spatial experience in Saudi Arabia. Anticipating this by giving adequate and real life visual spatial information was being perceived helpful by informers.